Postcolonial Antarctica and the memory of the Empire of Ice - N. Brazzelli (2014)
In 2012 the anniversary of Robert Falcon Scott’s arrival at the South Pole and of his death in the ice on his return journey has prompted new research on Scott and the Antarctic continent. The renaissance of Antarctic interests shows that Antarctica continues to be a source of fascination for the Western world as a place for the expression of individual bravery and endurance. However, the role of Antarctica as an imperial space in the British cultural imagination is now superseded by its status of postcolonial territory “owned” both by the former imperial nations and by postcolonial countries such as India or New Zealand. The 1959 Antarctic Treaty recognized to Great Britain an influential role in the international agreements that established international cooperation promoting scientific activity. At the same time, many other countries are directly involved in the project of making the “white continent” a natural reserve entirely devoted to science